2007
DOI: 10.1002/jbm.b.30949
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, salivary sorption and degree of conversion of dimethacrylate‐based polymeric matrixes

Abstract: This study investigated the relationship between the solubility, salivary sorption, and degree of conversion of dimethacrylate-based polymeric matrixes. Six polymeric matrixes produced by mixing bis-GMA, TEGDMA and UDMA dimethacrylate monomers were studied. Photoactivation was induced by camphoroquinone/ethyl N,N-dimethyl-4-aminobenzoate. The specimens were light-cured using an irradiance of 850 mW/cm(2) for 20 s. The solubility and sorption (microg/mm(3)) were measured after immersion in artificial saliva (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 31 publications
3
39
0
5
Order By: Relevance
“…The results of the present study were in accordance with those of previous studies (Aguilar et al, 2007;Musanje et al, 2009;Silva et al, 2008). Moreover, a previous study demonstrated that an increased amount of triethylene glycol dimethacrylate (TEGDMA) in an experimental dimethacrylate-based polymer matrix led to an increased conversion of the monomer (Goncalves et al, 2008). Similarly, in the present study, the flowable composite showed a higher DC due to the increased TEGDMA content.…”
Section: Discussionsupporting
confidence: 95%
“…The results of the present study were in accordance with those of previous studies (Aguilar et al, 2007;Musanje et al, 2009;Silva et al, 2008). Moreover, a previous study demonstrated that an increased amount of triethylene glycol dimethacrylate (TEGDMA) in an experimental dimethacrylate-based polymer matrix led to an increased conversion of the monomer (Goncalves et al, 2008). Similarly, in the present study, the flowable composite showed a higher DC due to the increased TEGDMA content.…”
Section: Discussionsupporting
confidence: 95%
“…4 The degradation of resin composites is a complex mechanism that depends on the characteristics of the composite, such as the size, 17 volume and type of inorganic filler, 2,4,18 matrix composition, and degree of conversion. 19 The most likely explanation for degradation is the presence of nanosized particles (5-20 nm) throughout the resin matrix, 7 which results in less space between the particles, and ultimately more protection of the softer resin matrix 4,20 and less filler plucking, 20 compared with other types of resins. This leads to lower resin porosity 21 and improved abrasion resistance of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Monomers like UDMA, Bis-GMA, and TEGDMA contain polar groups such as -OH-, -O-, and -NH-. These groups increase the material's hydrophilicity, 19 probably making it more prone to salivary sorption; 17 however, these factors cannot be considered to influence this study, since they were standardized for all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most probably, this behavior was influenced by the similarity in DC% among matrixes (Table 2). In fact, previous studies have already shown that solubility correlates well with degree of conversion 4,28) .…”
Section: Discussionmentioning
confidence: 91%
“…In general, resin composites comprise three phases: a organic matrix formed by a mix of bi-functional methacrylate monomers, inorganic filler particles and a silane-coupling agent that chemically bonds the organic matrix to the filler particles. These three phases strongly influence the materials' properties 4,5) . Irrespective of recent and important developments 1,2) , organic matrixes of resin composites are still composed of bi-functional methacrylate momomers 6) .…”
Section: Introductionmentioning
confidence: 99%